'Cutting the Colonial Cord'? Tensions of Value and the Relationship between Tokelau and New Zealand. Issue 2 (20th July 2021) - Hoëm, Ingjerd
ABSTRACT: This article discusses concepts of self‐government, dependence and independence in the light of Tokelau and New Zealand practices. Kin‐based forms of mutual dependence are compared with the demands for specific forms of self‐governance practiced by the New Zealand administration. Tensions of value have emerged between village based political leadership, and the public servants of the administrative infrastructure. The smallness of Tokelau's land area is complemented by its considerable maritime resources secured by an Exclusive Economic Zone. Tokelau's need for New Zealand administrative support to administer its fishing quotas, and for military policing of its maritime boundaries, makes Tokelau dependent on the greater power. The relationships of dependency going the other way, that is New Zealand's dependence on the marine wealth of Tokelau and its strategic value as Pacific partner, are largely obscured by the policies that demand Tokelau reaches an internationally approved standards of governmental practices for it to be able to govern its own affairs. The two forms of dependency, one based on reciprocity and mutuality, and the other, rooted in an economic logic of self‐sufficiency are entangled in everyday life in Tokelau. However, the practices of economic self‐sufficiency work over time to erode the viability of the local subsistence economy.